Flavonoids: promising natural compounds against viral infections - Zakaryan, Hovakim; Arabyan, Erik; Oo, Adrian; Zandi, Keivan (Archives of virology, 2017)
Flavonoids are widely distributed as secondary metabolites produced by plants and play important roles in plant physiology, having a variety of potential biological benefits such as antioxidant, anti-inflammatory, anticancer, antibacterial, antifungal and antiviral activity. Different flavonoids have been investigated for their potential antiviral activities and several of them exhibited significant antiviral properties in in vitro and even in vivo studies. This review summarizes the evidence for antiviral activity of different flavonoids, highlighting, where investigated, the cellular and molecular mechanisms of action on viruses. We also present future perspectives on therapeutic applications of flavonoids against viral infections.